Sustainable Innovation in Road Engineering: The Use of Recycled Materials in Asphalt Mixtures (Jóvenes en la Ciencia, 2026)
The use of recycled materials such as tire rubber granules (TRG) and PET plastic in asphalt mixtures represents a sustainable alternative for pavement construction. Research shows that these materials improve mechanical properties such as stability, moisture resistance, and long-term performance, meeting current regulations. In addition to reducing waste, they offer economic benefits by lowering maintenance costs and increasing road durability, establishing themselves as a viable solution for a more sustainable and efficient road infrastructure.